Radiative properties of porous fly ash particles based on the particle superposition model. (January 2022) - Tang, Yanxia; Zhu, Keyong; Huang, Yong
Highlights: The particle superposition model offers a general model for porous particles. Concentrated, dispersed, and cratered surface porous particle models are generated. The pore dispersed distribution affects radiative properties of porous particles. Abstract: Research on the radiative properties of porous fly ash particles is highly important for accurately assessing the radiative impact of particles and their remote-sensing measurements. We develop a general porous particle model based on the particle superposition model for flexibly constructing variations in the particle shape, size parameters, porosity, pore size, and pore dispersed distribution. Concentrated, dispersed, and cratered surface porous particle models are constructed to consider the effect of the distribution of pores on the radiative properties of porous particles. The radiative properties of porous fly ash particles are computed using the discrete dipole approximation (DDA) method. The effects of the porosity, pore size, pore dispersed distribution, and overall particle size on the radiative properties are analyzed. Generally, the increase of pore size promotes forward scattering intensity and weakens backward scattering intensity. The more dispersed pore distribution promotes stronger backward scattering intensity and stronger oscillations of the degree of linear polarization. Measurement of the Mueller matrix element S 11 in different scattering angle regions can be descriptive of the pore distribution. The dispersed pore distribution promotes the extinction cross sections. The asymmetry parameter decreases with the increase of porosity and increases with increasing pore size. In addition, it is necessary to consider both the particle size and pore dispersed distribution for investigating the effect of porosity and pore size on the single-scattering albedos of porous fly ash particles.